Furrow‐and‐Ridge Morphology on Rockglaciers Explained by Gravity‐Driven Buckle Folding: A Case Study From the Murtèl Rockglacier (Switzerland). (11th December 2014) - Frehner, Marcel; Ling, Anna Hui Mee; Gärtner‐Roer, Isabelle
Abstract Rockglaciers often feature a prominent furrow‐and‐ridge topography. Previous studies suggest that this morphology develops due to longitudinal compressive flow during rockglacier creep; however, no satisfactory mechanical/physical model has been provided explaining both the observed characteristic wavelength and the growth rate necessary to amplify the structure to its final size. Our study identifies viscous buckle folding as the dominant process forming the furrow‐and‐ridge morphology on rockglaciers. Buckle folding is the mechanical response of layered viscous media to layer‐parallel compression. The Murtèl rockglacier (Switzerland) exhibits a spectacular furrow‐and‐ridge morphology and is chosen as a case study. Its well‐determined internal structure can be approximated by two layers: the upper 3–5 m thick active layer consisting mainly of rock boulders and fragments above a thick, almost pure, ice layer, both assumed to exhibit viscous rheology. We analysed a high‐resolution digital elevation model of the Murtèl rockglacier using analytical buckle‐folding expressions, which provide quantitative relationships between the observed wavelength, the layer thickness and the effective viscosity ratio between the folded layer and the underlying ice. Based on this geometrical and rheological information, we developed a finite‐element model to simulate dynamical gravity‐driven two‐dimensional rockglacier flow. A buckling instability of the upper layer develops and amplifies self‐consistently, reproducing several key features of the Murtèl rockglacier (wavelength, amplitude and distribution of the furrow‐and‐ridge morphology), as well as the quasi‐parabolic deformation profile observed in boreholes. Comparing our model with published surface flow velocities constrains the time necessary to produce the furrow‐and‐ridge morphology to about 1000–1500 years. Copyright © 2014 John Wiley & Sons, Ltd.